Effect of Huang-Lian Jie-Du Decoction on Glucose and Lipid Metabolism in Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Hu, Zhipeng; Yang, Maoyi; Liu, Ya; Yang, Qiyue; Xie, Hongyan; Peng, Sihan; Gao, Juan; Xie, Chunguang (Frontiers in Pharmacology, 2021)
Abstract Background: Type 2 diabetes mellitus (T2DM) is a heterogeneous disease characterized by persistent hyperglycemia. Huang-Lian Jie-Du decoction (HLJDD) is a traditional Chinese medicine formula which is widely used in treating T2DM in China. A thorough understanding of current body of evidence is needed. Objective: this study aims to summarize the clinical evidence of HLJDD for T2DM to provide an up-to-date and accurate understanding of this issue for research and clinical practice. Methods: Six databases were searched from inception to June 27, 2020 without language and publication status restrictions and randomized controlled trials about HLJDD on T2DM were included. Two evaluators searched and screened citations independently. Risk of bias was assessed by 2019 version 2 of the Cochrane risk-of-bias tool for randomized trials (RoB2). Risk ratio (RR) with 95% confidence interval (CI) was used as an effect measure for dichotomous outcomes and mean difference (MD) with 95% CI was used for continuous outcomes. Subgroup analyses and sensitivity analyses were carried out. Results: Nine studies including 811 participants were included in this study. The overall risk of bias was high risk. Compared with metformin alone, combination treatment of HLJDD and metformin may result in a reduction in HbA1c, FBG, 2hPG, HOMA-IR and an improved lipid metabolism. Evidence comparing HLJDD and metformin or no intervention or placebo was insufficient. The quality of evidence was low. Conclusion: Current evidence about HLJDD on T2DM is still uncertain and more high-quality studies are needed to firmly establish the clinical efficacy and safety of HLJJD.